A Rare Cause of Low Back Pain in Pregnancy: Pregnancy Associated Osteoporosis - Alparslan Yetişgin; Dilek Şen Dokumacı; Mehmet Ali Eren; Hamza Karabağ (Galenos Yayinevi, 2016)
Pregnancy associated osteoporosis is a rare entity seen at the third trimester of first pregnancy or early postpartum period. It does not recur frequently in the subsequent pregnancies; however, it might lead to various complications unless it is treated. In this paper, we presented a woman diagnosed with pregnancy-associated osteoporosis with back pain at the 6th month of the pregnancy in order to discuss the points to be taken into consideration in the diagnosis/differential diagnosis and treatment options of pregnancy associated osteoporosis.